Comparison of celery (Apium graveolens L.) collenchyma and parenchyma cell wall polysaccharides enabled by solid-state 13C NMR. (February 2016) - Zujovic, Zoran; Chen, Da; Melton, Laurence D.
Highlights: NMR was used to study the collenchyma and parenchyma cell walls of celery. NMR showed the differences between collenchyma and parenchyma cell walls. Arabinan signals were more evident in the collenchyma spectrum. Galactan showed a much stronger resonance in the parenchyma spectrum. Non-esterified pectin has a greater role in cell–cell adhesion in collenchyma. Graphical abstract: Abstract: Collenchyma cells with their thickened walls are one of specific mechanical support tissues for plants, while parenchyma cells are thin walled and serve multiple functions. The parenchyma tissue is what you enjoy eating, while collenchyma, because of its fibrous nature, is not so attractive. Celery is a useful model for comparing the cell walls (CWs) of the two cell types such as collenchyma and parenchyma. However, to date, the structural characteristics of collenchyma and parenchyma cell walls from the same plant have not been compared. Monosaccharide composition suggested the collenchyma cell walls contained less pectin but more hemicellulose in comparison to parenchyma. High-resolution solid-state NMR spectra of highly mobile pectins revealed that the arabinan signals were more evident in the collenchyma spectrum, while galactan showed a much stronger resonance in the parenchyma spectrum. In addition, methyl esterified and non-esterified galacturonic acid signals were observed in parenchyma CWs, but only the latter one appeared in the collenchyma. The ratio of cellulose surface/interior obtained from CP/MAS spectra for collenchyma suggested the cellulose microfibrils were 2.4 nm, while in the parenchyma, these were somewhat larger. X-ray diffraction indicated the size of the cellulose microfibrils were the same for both types of CWs.